PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN WILAYAH KABUPATEN MAMUJU UTARA - Nastuti, Gusti Ayu; Laapo, Alimuddin; S. Hamzens, Wildani Pingkan (AGROTEKBIS, 2018)
The purpose of this research is to know (1) Agricultural Sector Contribution toThe Economy In Mamuju Utara Regency, (2) subsector base and non base of agriculture sector in Regency in Mamuju Utara Regency, and (3) change of position of agriculture sector and subsector in Mamuju Utara Regency. This research was conducted in North Mamuju Regency conducted in March-April 2017. This secondary data was obtained from Central Bureau of Statistics (BPS) Mamuju Utara Regency, West Sulawesi Province. Data analysis tool used in this research is Contribution Analysis, Quantity Location Analysis (LQ) and Dynamic Location Quotient (DLQ).The results showed that the analysis of agricultural sector contribution to the formation of GRDP in Mamuju Utara Regency at 2015 amounted to 41.87%. LQ analysis showed that the agricultural sector in Mamuju Utara Regency from 2011-2015 to the base sector with an average LQ of 1.42. The DLQ analysis of the agricultural sector provides a value of 1.53. This indicates that the agricultural sector in Mamuju Utara Regency will remain the base in the future.